Analysis of tinnitus severity and associated risk factors in patients with chronic otitis media: data from the multinational collaborative Chronic Otitis Media Questionnaire-12 study. Issue 12 (10th December 2022) - Tailor, B V; Phillips, J S; Nunney, I; Yung, M W; Doruk, C; Kara, H; Kong, T; Quaranta, N; Peñaranda, A; Bernardeschi, D; Dai, C; Kania, R; et al.
Abstract: Background: Subjective tinnitus is a common symptom, and there is often an underlying otological cause. This study investigated the degree of tinnitus-related annoyance in patients with chronic otitis media and analysed whether associations with tinnitus severity exist. Method: The multinational collaborative Chronic Otitis Media Questionnaire-12 study collected prospective data on 478 adult patients suffering from chronic otitis media across 9 otology referral centres in 8 countries. Based on this dataset, we investigated tinnitus severity using participant responses to item 7 of a native version of the Chronic Otitis Media Questionnaire-12. Results: With respect to tinnitus severity, 23.8 per cent, 17.4 per cent, 15.5 per cent, and 43.4 per cent of participants reported no, minor, moderate, and major inconvenience or greater, respectively. The absence of ear discharge, absence of cholesteatoma, and poorer disease-specific health-related quality-of-life were associated with increased tinnitus severity in patients with chronic otitis media, whereas age, hearing disability and geographical region showed no association. Conclusion: This analysis provided novel insight into potential risk factors for tinnitus in patients with chronic otitis media.